Short Communication: In Utero HIV Infection Is Associated with an Increased Risk of Nevirapine Resistance in Ugandan Infants Who Were Exposed to Perinatal Single Dose Nevirapine - Fowler, G. Mary (Mary Ann Liebert, Inc, 2009)
Use of single dose nevirapine (sdNVP) to prevent HIV mother-to-child transmission is associated with the emergence of NVP resistance in many infants who are HIV infected despite prophylaxis. We combined results from four clinical trials to analyze predictors of NVP resistance in sdNVP-exposed Ugandan infants. Samples were tested with the ViroSeq HIV Genotyping System and a sensitive point mutation assay (LigAmp, for detection of K103N, Y181C, and G190A). NVP resistance was detected at 6–8 weeks in 36 (45.0%) of 80 infants using ViroSeq and 33 (45.8%) of 72 infants using LigAmp. NVP resistance was more frequent among infants who were infected in utero than among infants who were diagnosed with HIV infection after birth by 6–8 weeks of age. Detection of NVP resistance at 6–8 weeks was not associated with HIV subtype (A vs. D), pre-NVP maternal viral load or CD4 cell count, infant viral load at 6–8 weeks, or infant sex. NVP resistance was still detected in some infants 6–12 months after sdNVP exposure. In this study, in utero HIV infection was the only factor associated with detection of NVP resistance in infants 6–8 weeks after sdNVP exposure.
Keywords: Uganda; HIV; HIV infection; Nevirapine resistance; Ugandan infants; Perinatal Single dose nevirapine